The Implementation of Proper Drug Distribution Methods in Handling Cold Chain Products at a Major Pharmaceutical Distributor in Manado City - Widya Astuty Lolo; Weny Indayani Wiyono; Deby Afriani Mpila; Fridly Manawan (Riviera Publishing, 2026)
Good Drug Distribution Practices (CDOB) is a drug distribution method that aims to ensure quality in the distribution process according to the requirements and intended use. Pharmaceutical Wholesalers (PBF) must ensure that the quality and efficacy of products during distribution are in accordance with applicable laws and regulations including Cold Chain Products (CCP) or cold chain products, namely vaccines, biological products, oncology treatments, several types of insulin and other medicines. Pharmaceutical Wholesalers (PBF) play an important role in handling and distributing preparations, including preparations that are sensitive to environmental conditions such as CCP products. This study aims to evaluate the implementation of CDOB in handling CCP products at one of the Pharmaceutical Wholesalers (PBF X) located in Manado City using the BPOM RI self-inspection checklist. The study was conducted in July 2025 with an observational method that is descriptive and evaluative. The results of the study indicate that PBF X has fulfilled all aspects of cold chain product handling related to receipt, storage, and distribution. It can be concluded that PBF X has implemented CDOB aspects in accordance with applicable regulations